Pesantren: Between Challenges and Hopes - Jannah, S. Fathiyatul; Jannah, Faridatul; Endang Maisuri, Desi; Kurniawan, Cecep Soleh (STAI Publisistik Thawalib Jakarta, 2023)
TThe pesantren aims to foster religious values, shape character, and teach knowledge, ethics, and independence through a unique system and varied curriculum to produce a morally upright Muslim generation. The research aims to describe the challenges and hopes of education in pesantren. The research method used is descriptive qualitative with a literature study approach. Data collection techniques include documentation study, and data processing involves reduction, data presentation, and conclusion drawing. Research results show that challenges in pesantren involve patience, sincerity, and obedience. Patience is important in facing tests and regulations, sincerity directs actions to Allah, and obedience reflects the character of the students. The hope of pesantren is to produce graduates who are beneficial to society. Students are expected to turn fatigue into worship, gain beneficial knowledge, and dedicate themselves to the kyai with sincerity. Beneficial knowledge and barakah dedication are signs of success, forming morally upright, independent, and socially responsible students. These three elements shape a resilient and pious character. Conclusion: The challenges and hopes of pesantren shape students to be morally upright, knowledgeable, independent, and pious.